Derris Scandens Benth Extract Radiosensitizes HT-29 Colon Cancer Cells - Hematulin, Arunee; Ingkaninan, Kornkanok; Limpeanchob, Nanteetip; Sagan, Daniel (Siriraj Medical Journal, 2020)
Objective: To evaluate the radiosensitizing potential of Derris scandens extract in a human colon cancer cell model. Methods: The radiosensitizing effect of D., scandens extract on human colon cancer cells (HT-29) and non-cancerous human retinal epithelial cells (RPE) was determined by cell survival and micronuclei analysis after irradiation. Cell cycle distribution was analyzed by a flow cytometer. Results: D. scandens extract powerfully increases the radiosensitivity of HT-29 cells, but is less toxic and does not affect the radiosensitivity of RPE cells. Furthermore, the extract was found to reduce radiation-induced G2/M phase arrest in HT-29 cells, but not in RPE cells. Conclusion: D., scandens extract may have potential as a radiosensitizer for cancer treatment.